Bases para un futuro derecho europeo de la jurisdicción voluntaria - Liébana Ortiz, Juan Ramón (Revista General de Derecho Público Comparado, 2020)
After confirming the need for an European Union harmonization on the laws governing the voluntary jurisdiction, this paper examines the national legislations from Hungary, Slovenia, France, Germany, Italy, Finland and Sweden in order to identify a common core to create a foundation upon which developing a future European Law on voluntary jurisdiction taking as a point of reference the Spanish legislation.
Non-contentious jurisdiction: proposals for a new european legal framework
Keywords: voluntary jurisdiction; non-contentious proceedings; European Law; Comparative Law; Emerging